C–H Activation at a Bidentate Ligand Coordinated to Palladium(II) – an Electrophilic Attack Supported by an External Base. Issue 16 (30th April 2014) - Cayir, Merve; Ghoochany, Leila Taghizadeh; Walli, Adam; Busch, Mark; Sun, Yu; Meyer, Franc; Bräse, Stefan; Thiel, Werner R.
Abstract: 2‐(2‐Phenylaminopyrimidin‐4‐yl)pyridines undergo C–H activation at the phenyl ring in the ortho position to the amine nitrogen atom when reacted with (PhCN)2 PdCl2 and finally form N, N, C ‐coordinated palladium(II) complexes in high yields. Five differently substituted complexes were synthesized and characterized by spectroscopy and X‐ray structure analysis. The reaction mechanism for the formation of these complexes was elucidated by kinetic experiments, which allowed the calculation of the activation parameters of the complex formation. Abstract : 2‐(2‐Anilinopyrimidin‐4‐yl)pyridines undergo rapid bidentate N, N coordination to palladium dichloride followed by C–H activation at the ortho position of the aniline fragment. The mechanism of this process was elucidated by UV/Vis kinetic investigations, which proved that it follows an electrophilic aromatic substitution route.